Synthetic K+ Channels Constructed by Rebuilding the Core Modules of Natural K+ Channels in an Artificial System - Xin, Pengyang; Xu, Linqi; Dong, Wenpei; Mao, Linlin; Guo, Jingjing; Bi, Jingjing; Zhang, Shouwei; Pei, Yan; Chen, Chang‐Po (Angewandte Chemie International Edition, 2023)
Different types of natural K+ channels share similar core modules and cation permeability characteristics. In this study, we have developed novel artificial K+ channels by rebuilding the core modules of natural K+ channels in artificial systems. All the channels displayed high selectivity for K+ over Na+ and exhibited a selectivity sequence of K+≈Rb+ during the transport process, which is highly consistent with the cation permeability characteristics of natural K+ channels. More importantly, these artificial channels could be efficiently inserted into cell membranes and mediate the transmembrane transport of K+, disrupting the cellular K+ homeostasis and eventually triggering the apoptosis of cells. These findings demonstrate that, by rebuilding the core modules of natural K+ channels in artificial systems, the structures, transport behaviors, and physiological functions of natural K+ channels can be mimicked in synthetic channels. Rebuilding the core modules of natural K+ channels in an artificial system has led to a biomimetic K+ channel. This channel possesses similar structural features as the natural version, which enables it to replicate the transport behavior and biological function of natural K+ channels.